Tolerância à salinidade avaliada em genótipos de arroz, cultivados ex vitro e in vitro - Benitez, Letícia Carvalho (2008)
Plants under natural conditions are exposed to several environmental stresses which affect their metabolism. Among them, soil salinity is one of the most serious problems in irrigated agriculture. Trying to identify genetic variability for this character, the main goal of this work was to evaluate the germination and the initial development of plantlets of 10 rice genotypes under salt stress. The plantlets were cultivated ex vitro and in vitro, and many morphological characters were used to phenotype their responses. The investigations were performed ex vitro in the greenhouse and in vitro in culture media with NaCl concentrations of 0, 68, 136 and 204 mM added to a nutrient solution and to culture media, respectively. After 21 days from the beginning of each experiment, plantlet emergence and seed germination in vitro were evaluated. Other characters measured were shoot length, number of leaves, leaf area, root length, number of roots and fresh and dry mass of aerial part and radicular system. Analysis of variance, regression fitting, percentage of reduction and dissimilarity analysis were performed. The salinity damages were seen only at the initial phase of germination and plantlet emergence except on 204 mM concentration which was inhibitory to in vitro seed germination. All measured characters had their development reduced in saline substrate. The characters average shoot area, shoot biomass and root biomass were the most sensitive to NaCl and the characters leaf and root number were the less affected by the salinity excess. The genotypes showed different responses in both experimental conditions. The genotypes formed three groups when an UPGMA hierarchal method was applied to both system of cultivation. Five and two groups were found when Tocher optimization method was applied to in ex vitro and in vitro data, respectively. The variables average shoot area and average root dry mass contributed more to similarity between genotypes ex vitro, while the average shoot and root weight were the most contributing for the in vitro dissimilarity. The variable shoot length was the one that less contributed to genotype discrimination in both cultivation systems. It is concluded that the genotype BRS Bojuru presented the highest tolerance to salinity while BRS Ligeirinho showed the lowest tolerance in both investigations.